A Report for Ratnagiri District of Maharashtra State Study on Project Oriented Planning vs Schematic Planning Process - Case Studies as Related to Utilisation of Wasteland for Development of Rainfed Horticulture - Planning Commission (Planning Commission, 1997)
Ratnagiri District of Maharashtra State has cot more than 30 per cent area under wastelands of various categories on account of its being located in the western coastal zone where the mean average rainfall received mostly during the monsoon season is very high exceeding 3000 mm and steep terrain slope. Coupled with the geomorphological and agro-climatic phenomena, wanton deforestation and removal of vegetative cover due to uncontrolled grazing by non-descript cattle of the local breed have also accelerated the process of soil erosion.
Planning Commission Government of India
Planning Commission Government of India